2013
DOI: 10.1111/jsbm.12092
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Flexibility Practices in SMEs: Relationship with Performance via Redundancies, Absenteeism, and Financial Turnover

Abstract: This workplace flexibility study uses primary data on private sector Small and Medium Enterprises (SMEs) Introduction: Motivation for Researching Workplace Flexibility in SMEsConditions of weak demand are, by definition, problematic for firms, conflicting with organisational interests to maintain production and protect human capital assets. One potential response to recessionary pressures relates to an increase in workplace flexibility. This approach might enable firms to adapt to new market conditions whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 109 publications
(205 reference statements)
5
34
0
4
Order By: Relevance
“…Mesu et al (2013) found that SMEs use both functional and working time flexibility practices. Whyman and Petrescu (2015) found also in their UK-study that SMEs use all kinds of workplace flexibility practices, such as functional, working time and contractual practices. Mihail (2004) found that Greek SMEs rely more on internal flexibility practices, such as functional and time flexibility practices.…”
Section: Theory On Labour Flexibility In Smesmentioning
confidence: 89%
See 1 more Smart Citation
“…Mesu et al (2013) found that SMEs use both functional and working time flexibility practices. Whyman and Petrescu (2015) found also in their UK-study that SMEs use all kinds of workplace flexibility practices, such as functional, working time and contractual practices. Mihail (2004) found that Greek SMEs rely more on internal flexibility practices, such as functional and time flexibility practices.…”
Section: Theory On Labour Flexibility In Smesmentioning
confidence: 89%
“…One of the challenges of SMEs is their ability to cope with demand fluctuations (Wilkinson, 1999; Matejun, 2014; Whyman and Petrescu, 2015; Kotey, 2017). Given their impact on the labour market, it is relevant to know how small enterprises deal with flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…; Cegarra‐Leiva et al . ; Whyman and Petrescu ). However, only Atsumi () explores the processes of mutual adjustment, describing cases of female‐dominated firms in Japan that employ locally, and are characterized by close relationships and a long‐term view of performance.…”
Section: Management Of the Return To Workmentioning
confidence: 97%
“…Small and medium‐sized enterprise mutual adjustments are often made silently and rely on presumptions of the other party's interests (Wapshott and Mallett ) and, in maternity management, are likely to be shaped by gendered assumptions about mothering work and mothers’ capacities. The literature on maternity management in SMEs largely neglects these silent negotiations, although there is evidence of small employers’ biased expectations of mothers (Woodhams and Lupton ) and that women's assumptions about organizational resource constraints and colleagues’ interests can curtail their expectations of adjustments (Atsumi ; Whyman and Petrescu ).…”
Section: Management Of the Return To Workmentioning
confidence: 99%
“…The literature on SMEs has recognized the ability of these firms to adapt their business model; moreover, it has identified numerous factors contributing to innovation such as management strategic orientation, networking, customer demand, and the internal culture. Also important is their flexibility to adjust inputs, improve technological methods and products continuously, and modify prices rather quickly according to changes in the external environment (Reid, 2007;Laforet, Tan, 2006;Whyman, Petrescu, 2013).…”
Section: Innovation As the Driving Force To Competementioning
confidence: 99%